FAKTOR YANG BERHUBUNGAN DENGAN PEMBERIAN ASI EKSKLUSIF PADA BAYI (0-6 BULAN) DI KELURAHAN BANTAN KECAMATAN MEDAN TEMBUNG TAHUN 2013 - Yesica Siallagan; Erna Mutiara; Yusniwarti Yusad (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
Exclusive breasfeeding means that an infant receives only breastmilk with no additional foods or liquids, not even water for the infant of 0-6 months. Based on data of National Institute of Health Research & Development in 2010 only 15,3% infants in Indonesia got exclusive breastfeeding whereas the expected target was 80%. Data from Health Profile of Medan Municipality Health Office in August 2011 there were 174 (4,08%) infants got exclusive breastfeeding. This low coverage gave rise to remaind health problems in the babies that it can bring impact on the quality of human resources in the future. The purpose of this study was to know factors associated with exclusive breastfeeding to the baby of 0-6 months old the Bantan Village, Medan Tembung Sub District in 2013. The design of this study was cross-sectional. The population in this study were all mothers with babies of 7-12 months old the Bantan Village, Medan Tembung Sub District amounted 181 mothers. The technique of sampling was purposive sampling and 100 of them were selected to be sample. Data were collected by interview using questionnaires. Data analysis included univariate and bivariate by using chi-square test. The results of this study showed that 100 respondents, from data analisis stases of included univariate and bivariat only four respondent (4,0%) gave exclusive breastfeeding. It was found there was relationship between knowledge (p = 0,023), education level (p = 0,018) and the factor of tradition/habit (p = 0,002) with exclusive breastfeeding. Medan Municipality Health office is expected to increase knowledge of the mother through health workers at Mandala Health Center by giving extention or counseling about exclusive breasfeeding and the impact of the other foods and drinks given to infants before the age of 6 months. Key words : Exclusive breastfeeding knowledge, education and tradition/habit